1994
DOI: 10.1099/0022-1317-75-9-2319
|View full text |Cite
|
Sign up to set email alerts
|

Role of envelope glycoproteins gI, gp63 and gIII in the invasion and spread of Aujeszky's disease virus in the olfactory nervous pathway of the pig

Abstract: One-week-old pigs were infected intranasally with the Ka strain of Aujeszky's disease virus (ADV) or with mutants that were lacking the non-essential envelope glycoproteins gI, gp63 or glII. The invasion and spread of these strains in the olfactory nervous pathway were examined by assessing virus levels and by localizing viral antigens in the olfactory mucosa representing the first neuronal level, in the olfactory bulb representing the second neuronal level and in the lateral olfactory gyrus, the rostral perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 22 publications
4
62
0
Order By: Relevance
“…the olfactory, trigeminal, sympathetic and parasympathetic pathways (Babic et al, 1996). These results confirm and extend observations from other laboratories that PrV or HSV-1 gE is implicated in transneuronal transfer rather than in penetration and multiplication in first order neurons (Card et aL, 1992;Ba[an et aI., 1994;Kritas et al, 1994, Mulder et a]., 1994Dingwell et al, 1995;Standish et al, 1994).…”
Section: Introductionsupporting
confidence: 80%
“…the olfactory, trigeminal, sympathetic and parasympathetic pathways (Babic et al, 1996). These results confirm and extend observations from other laboratories that PrV or HSV-1 gE is implicated in transneuronal transfer rather than in penetration and multiplication in first order neurons (Card et aL, 1992;Ba[an et aI., 1994;Kritas et al, 1994, Mulder et a]., 1994Dingwell et al, 1995;Standish et al, 1994).…”
Section: Introductionsupporting
confidence: 80%
“…In contrast, the nervus trigeminus with all of its branches converges in the trigeminal ganglion leading to the pons and the brain stem. Therefore, after primary replication in the nasal mucosa, these two routes repre-sent the major ways of viral neuroinvasion toward the CNS (20,21,30), and the olfactory bulb and the sensory ganglia are major sites of latent virus (40).…”
mentioning
confidence: 99%
“…In naïve pigs, PrV replicates first in the respiratory tract, mainly in the upper part, consisting of the nasal cavity, tonsils and the oropharynx upon intranasal/peroral inoculation. It infects primarily the epithelial cells and within 24 h it crosses the basement membrane in order to infect all cell types in the underlying tissues in a plaquewise fashion (fibrocytes, endothelial cells, mononuclear cells) [31,32,39,56,57,72]. How the virus penetrates easily through the mucus layer barrier on top of the epithelial cells and crosses the basement membrane barrier is not known and deserves more indepth studies.…”
Section: Virus-respiratory Tract Interactionsmentioning
confidence: 99%
“…PrV gC and gI negative mutants behaved like the wild type virus with respect to the number and size of the foci of infected cells in the mucosa/submucosa. In contrast, the absence of gE and gD resulted in a reduced number of infected cells and gave foci with smaller dimensions [31,32,40]. Concerning the enzymes, it was demonstrated that the absence of viral ribonucleotide reductase, dUTPase and US3-encoded protein kinase was reducing virus excretion in pigs, indicating that the replication was clearly affected [9,20,23].…”
Section: Virus-respiratory Tract Interactionsmentioning
confidence: 99%